Pengaruh Edukasi Pola Makan dan Pola Hidup Bersih dan Sehat terhadap Penyembuhan Pasien Demam Tifoid di RS Ibnu Sina YW-UMI Makassar - Yudia Nurul Eliza; Hasta Handayani Idrus; Febie Irsandi Syahruddin; Yusriani Mangarengi; Aryanti Bamahry (Universitas Muslim Indonesia, 2023)
Typhoid fever is one of the 10 most inpatients in Ibnu Sina Hospital in Makassar. A dietary habit and a less clean and health life behavior cause Salmonella typhi germs to easily enter the digestive tract through fecal andoral passages that enter the human body from contaminated food and drink. This study aims to determine the influence of dietary education and a clean and healthy lifestyle on the healing of typhoid fever patients at Ibnu Sina YW-UMI Hospital Makassar. Type of research used observational analytics with a cross-sectional study approach. The sampling technique uses a total sampling of 30 sampels and is processed using the Fisher test. From the statistical data, it shows that there is a significant influence of dietary habit on healing typhoid fever patients with a r value = 0.000, while for a clean and healthy life behavior, it shows no influence before and after education with a r value = 0.330.